2021
DOI: 10.1002/aic.17144
|View full text |Cite
|
Sign up to set email alerts
|

Second interfacial polymerization of thin‐film composite hollow fibers with amine‐cyclodextrins for pervaporation dehydration

Abstract: High performance thin‐film composite (TFC) hollow fiber membranes have been developed for pervaporation dehydration by second interfacial polymerization (SIP) modification with three kinds of amine‐functionalized β‐cyclodextrin (amine‐CDs), which were synthesized by modifying β‐CD with ammonia, ethylenediamine (EDA), and tris(2‐aminoethyl)amine, respectively. The chemical properties of amine‐CDs and SIP‐modified TFC membranes were characterized by various techniques. The effects of amine‐CD type and SIP parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The operation temperature ranges from 40 °C to 80 °C. The pervaporation performance was assessed by total flux ( J , g m −2 h −1 ) and separation factor ( α ) as defined below: 50,51 where w , A , and t refer to the weight of the permeate (g), the effective membrane area (cm 2 ), and the permeation time (h), respectively. x f and y p are the weight fractions of alcohol in feed and permeate, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation temperature ranges from 40 °C to 80 °C. The pervaporation performance was assessed by total flux ( J , g m −2 h −1 ) and separation factor ( α ) as defined below: 50,51 where w , A , and t refer to the weight of the permeate (g), the effective membrane area (cm 2 ), and the permeation time (h), respectively. x f and y p are the weight fractions of alcohol in feed and permeate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The operation temperature ranges from 40 1C to 80 1C. The pervaporation performance was assessed by total flux (J, g m À2 h À1 ) and separation factor (a) as defined below: 50,51…”
Section: Pervaporation Testmentioning
confidence: 99%
“…Among the numerous methods for preparing PV membranes, interfacial polymerization (IP) is an effective method for fabricating the thin and defect-free thin-film composite (TFC) membranes, which is produced by a rapid reaction between the aqueous and organic phase monomer at the interface. [5][6][7] The physical and chemical properties of the monomer could significantly influence the morphological structure of the final polyamide layer. The researchers have found that amine-rich aqueous monomer fabricated dense polyamide (PA) layer with better performance for dehydration, which facilitate the diffusion of water molecules in PV membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous methods for preparing PV membranes, interfacial polymerization (IP) is an effective method for fabricating the thin and defect‐free thin‐film composite (TFC) membranes, which is produced by a rapid reaction between the aqueous and organic phase monomer at the interface 5–7 . The physical and chemical properties of the monomer could significantly influence the morphological structure of the final polyamide layer.…”
Section: Introductionmentioning
confidence: 99%